Advances in research on the impact and mechanisms of pathogenic microorganism infections on pyroptosis - Shang, Pan; Gan, Mailin; Wei, Ziang; Hu, Shijie; Song, Lei; Feng, Jinkang; Chen, Lei; Niu, Lili; Wang, Yan; Zhang, Shunhua; Shen, Linyuan; Zhu, Li; et al. (Frontiers in Microbiology, 2024)
Pyroptosis, also known as inflammatory necrosis, is a form of programmed cell death characterized by the activation of gasdermin proteins, leading to the formation of pores in the cell membrane, continuous cell swelling, and eventual membrane rupture. This process results in the release of intracellular contents, including pro-inflammatory cytokines like IL-1β and IL-18, which subsequently trigger a robust inflammatory response. This process is a crucial component of the body’s innate immune response and plays a significant role in combating infections. There are four main pathways through which pathogenic microorganisms induce pyroptosis: the canonical inflammasome pathway, the non-canonical inflammasome pathway, the apoptosis-associated caspase-mediated pathway, and the granzyme-mediated pathway. This article provides a brief overview of the effects and mechanisms of pathogen infections on pyroptosis.